Observational study in physical state evaluation in a mexican sample during 2014 (European Journal of Health Research, 2015)
This is a transversal, observational and descriptive study with a random sample of 1.200.453 individuals selected from different sectors and country areas (inclusion criteria: anyone older than four years old willing to participate; exclusion criteria: anyone that notified being pregnant, have any chronic lung or cardiac disease, or psychomotor disorder). The objective was to know the results of the application of the designed tool for physical state evaluation in the elaboration of personalized recommendations. Making comparisons between genre and age risk groups were identified as well as the most influent factors. A health diagnose was build up for this sample, being the pilot of a preventive, diagnostic and tracing program. This program consists somatometric measurements and simple physical tasks among which, we find the Course- Navette, an internationally accepted test for cardiorespiratory capacity, with pre and post measurements of vital signs. We used a written informed consent based on the International Conference of Harmonization guidelines and approved by the Anahuac University Investigation and Bioethical Committee, obtained from the participants or legal guardians. Data analysis was made with the statistical program, SPSS, searching basically for central tendency measures, dispersion measures, and relative frequencies.
Keywords: Diet; exercise; sedentarism; obesity; mexicans